Hampered by historical paradigms – echinocandins and the treatment of Candida endocarditis. Issue 5 (20th November 2013) - Gardiner, B. J.; Slavin, M. A.; Korman, T. M.; Stuart, R. L.
Summary Infective endocarditis due to Candida sp. has a high mortality rate. Traditionally, management involves early surgery and prolonged amphotericin ± flucytosine. We report a case of Candida parapsilosis bileaflet mitral valve endocarditis cured with anidulafungin and fluconazole, and review the role of echinocandins in the management of Candida endocarditis.